On the Effects of Downstream Entry - Tyagi, Rajeev K. (Management Science, 1999)
We study the effects of entry in a downstream market where firms (e.g., Compaq and IBM; CVS and Safeway) buy an input (e.g., microprocessor, grocery items) from an upstream supplier (e.g., Intel, Procter & Gamble) and sell their output to consumers. We show demand conditions where, contrary to conventional wisdom, entry of a new downstream firm lowers the downstream-market output and increases the consumer price. Thus consumers may be better off with fewer sellers in such markets. We also show that this entry may cause the profit of each incumbent downstream firm to: (i) remain unchanged; (ii) decrease; or (iii) even increase. Also, for a class of widely used demand conditions, the supplier’s optimal price is shown invariant to the entry/exit of its downstream buyer firms. We classify all possible effects of downstream entry in terms of fundamental market demand conditions.